Low-grade evolution of clay minerals and organic matter in fault zones of the Hikurangi prism (New Zealand). (22nd January 2019) - Maison, Tatiana; Potel, Sébastien; Malié, Pierre; Ferreiro Mählmann, Rafael; Chanier, Frank; Mahieux, Geoffroy; Bailleul, Julien
ABSTRACT: Clay minerals and organic matter occur frequently in fault zones. Their structural characteristics and their textural evolution are driven by several formation processes: (1) reaction by metasomatism from circulating fluids; (2) in situ evolution by diagenesis; and (3) neoformation due to deformation catalysis. Clay-mineral chemistry and precipitated solid organic matter may be used as indicators of fluid circulation in fault zones and to determine the maximum temperatures in these zones. In the present study, clay-mineral and organic-matter analyses of two major fault zones – the Adams-Tinui and Whakataki faults, Wairarapa, North Island, New Zealand – were investigated. The two faults analysed correspond to the soles of large imbricated thrust sheets formed during the onset of subduction beneath the North Island of New Zealand. The mineralogy of both fault zones is composed mainly of quartz, feldspars, calcite, chabazite and clay minerals such as illite-muscovite, kaolinite, chlorite and mixed-layer minerals such as chlorite-smectite and illite-smectite. The diagenesis and very-low-grade metamorphism of the sedimentary rock is determined by gradual changes of clay mineral 'crystallinity' (illite, chlorite, kaolinite), the use of a chlorite geothermometer and the reflectance of organic matter. It is concluded here that: (1) the established thermal grade is diagenesis; (2) tectonic strains affect the clay mineral 'crystallinity' in the fault zone; (3) there is a strong correlation between temperature determined by chlorite geothermometry and organic-matter reflectance; and (4) the duration and depth of burial as well as the pore-fluid chemistry are important factors affecting clay-mineral formation.